"I don't know why they don't come": barriers to participation in cardiac rehabilitation - Digiacomo, Michelle; Thompson, S.; Smith, J.; Taylor, Kate; Dimer, L.; Ali, Mohammed; Wood, M.; Leahy, T.; Davidson, Patricia (CSIRO Publishing, 2010)
Objectives. To describe health professionals’ perceptions of Aboriginal people’s access to cardiac rehabilitation (CR) services and the role of institutional barriers in implementing the National Health and Medical Research Council (NHMRC) guidelines Strengthening Cardiac Rehabilitation and Secondary Prevention for Aboriginal and Torres Strait Islander peoples. Design. Qualitative study. Setting. Metropolitan and rural tertiary and community-based public CR services and Aboriginal health services in WA. Participants. Thirty-eight health professionals working in the CR setting. Method. Semistructured interviews were undertaken with 28 health professionals at public CR services and 10 health professionals from Aboriginal Medical Services in WA. The participants represented 17 services (10 rural, 7 metropolitan) listed in the WA Directory of CR services.Results. Emergent themes included (1) a lack of awareness of Aboriginal CR patients’ needs; (2) needs related to cultural awareness training for health professionals; and (3) Aboriginal health staff facilitate access for Aboriginal patients. Conclusions. Understanding the institutional barriers to Aboriginal participation in CR is necessary to recommend viable solutions. Promoting cultural awareness training, recruiting Aboriginal health workers and monitoring participation rates are important in improving health outcomes.What is already known about this subject? Significant health and social inequity exists for Aboriginal Australians. Despite the persisting high rates of morbidity and mortality related to cardiovascular disease in Aboriginal Australians, participation rates in cardiac rehabilitation remain low. What does this paper add? Despite widespread dissemination of NHMRC guidelines, there remains a disconnect between CR health professionals’ understandings and practices and the needs of Aboriginal people in WA. Increasing the volume and quality of cultural awareness training as well as access to Aboriginal health professionals are crucial in addressing this disparity.What are the implications for practitioners? Increasing the number and support of Aboriginal people trained as health professionals will assist the system to respond better to the needs of communities. Collaborative partnership models where Aboriginal and non-Aboriginal health professionals work together to increase mutual understanding are warranted.